TANGGA NADA HIBRID MELALUI KONSEP PENCIPTAAN MUSIK - Berehme Adyatmo Purba (Institut Seni Indonesia Yogyakarta, 2017)
This writing is in the background of the phenomenon of existing phenomena of some composers making works of musical composition. Dominate the idea of story-based musical creation (ektramusikal) in the academic environment, resulting in an imbalance of explanations of the work. The purpose of the author is to create a concept of formation of hybrid tone, to participate as part of a musical discussion such as conceptualization before the embodiment of the work. Then to know that the many background ideas of the creation problem from the intramusical aspect of the creation dominance of the extramusical element. Combining elements of music from two different types of classification ladder. The process of making these hybrid tones is the result of developing the concept of a pre-existing hybrid scale, beginning with an experiment of tone interval combinations. Hybridity-related because it uses two elements of music combined, to underlie the exposure of concepts such as systematic flow of two elements of music mixed from two musical cultures. So with this intention as a trigger for writers and composers who want to do concept development also strengthen the intramusikal argument in the creation that is done, thus enriching the discourse in the field of musical composition. Keywords: Scale, Hybrid, Creative Idea